2020
DOI: 10.4193/rhin20.544
|View full text |Cite
|
Sign up to set email alerts
|

Six month follow-up of self-reported loss of smell during the COVID-19 pandemic

Abstract: INTRODUCTION: Loss of smell and taste is now recognised as amongst the most common symptoms of COVID-19 and the best predictor of COVID-19 positivity. Long term outcomes are unknown. This study aims to investigate recovery of loss of smell and the prevalence of parosmia. METHODOLOGY: 6-month follow-up of respondents to an online surgery who self-reported loss of smell at the onset of the CO- VID-19 pandemic in the UK. Information of additional symptoms, recovery of loss of smell and the development of parosmia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
132
7
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(172 citation statements)
references
References 30 publications
(36 reference statements)
17
132
7
7
Order By: Relevance
“…The recovery in all cases was reported in another study in 28 days (43). A 6-month follow-up study on 434 individuals showed that over 70% had full or almost full recovery of loss of smell and about 2% of cases reported no improvements (44). It was also reported that over 40% of participants developed parosmia with the median interval of 2.5 months after the onset of smell dysfunction (44).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The recovery in all cases was reported in another study in 28 days (43). A 6-month follow-up study on 434 individuals showed that over 70% had full or almost full recovery of loss of smell and about 2% of cases reported no improvements (44). It was also reported that over 40% of participants developed parosmia with the median interval of 2.5 months after the onset of smell dysfunction (44).…”
Section: Discussionmentioning
confidence: 65%
“…A 6-month follow-up study on 434 individuals showed that over 70% had full or almost full recovery of loss of smell and about 2% of cases reported no improvements (44). It was also reported that over 40% of participants developed parosmia with the median interval of 2.5 months after the onset of smell dysfunction (44). Our study also showed that about 10% of cases with hyposmia/anosmia developed parosmia after 4 weeks of discharge that increased to over 30% after 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In the wake of the initial phase of the COVID-19 pandemic, several observational studies, patient groups and case series have reported persistent symptoms including reduced respiratory capacity [8], fatigue and hyposmia [9,10,11]. In a follow-up study of 143 Italians discharged after hospitalization due to COVID-19, 87.4% still experienced COVID-19-related symptoms at two months after symptom start, and more than half of the patients reported persistent fatigue [12].…”
Section: Introductionmentioning
confidence: 99%
“…The loss and dysfunction of olfaction due to SARS-CoV-2 has been reported to recover within weeks [5]. However, many studies have identified long-term complications of olfaction [4,6].…”
Section: Resultsmentioning
confidence: 99%
“…Agyeman et al [4] further reported 41% of 8438 COVID- 19 positive individuals experienced olfactory dysfunction. For the majority of individuals who experience distortions in olfaction, they tend to recover this sense within a month [5]. However, there is a growing body of evidence suggesting that the sense of smell can be impaired for longer periods of time after infection.…”
Section: Introductionmentioning
confidence: 99%